Preference reversals in dynamic decision‐making under uncertainty based on regret theory. (17th November 2022) - Guo, Sainan; Vetschera, Rudolf
Abstract: This research aims at preference reversals in dynamic adjusting decisions made by decision‐makers who have regretful emotions. Our model incorporates a utility function that includes the regretful feeling into outcomes under uncertainty. Then, by using the process of backward induction, it analyzes differences in the decisions of three types of decision‐makers with perfect rationality, partially anticipated regret, and fully anticipated regret. Finally, we apply this dynamic adjusting model to emergency plans in which decision‐makers need to choose the best action from multiple selections quickly to reduce the loss caused by disaster incidents and uncertainty. This model allows to compare decisions made by rational and irrational agents, which is a more realistic estimate and measure of several applications in the real life, such as medical services and emergency management.